Lean Management Genesis - Parkes Aneta (Management, 2015)
Lean Management is a philosophy and management concept, based on reduction of the waste and resources used in the process of producing goods and providing services. Lean Management genesis dates back to scientific management in America (for example concepts of H. Ford and F.W. Taylor) and quality management, including development of TQM concept. Japanese Toyota Production System has been inspired by chosen elements of these concepts, and then it evolved towards global concept called Toyota Way (which connects production rules with values and work attitude).